Spin-momentum locking as a source of spin-splitting anisotropy in inverted HgTe quantum wells - Maciej Kubisa; Krzysztof Ryczko (New Journal of Physics)
We show theoretically that Rashba spin–orbit coupling in gated heterostructures results in strong anisotropy of electron spin splitting. A simple analytical expression for the splitting energy is derived and shown to be in excellent agreement with multiband numerical calculations. Moreover, our theory successfully explains recent experimental results for inverted HgTe quantum wells.